PERBANDINGAN EFEKTIVITAS PELVIC TILT EXERCISE DAN SLOW DEEP BREATHING TERHADAP NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Adinda Putri Sari Dewi; Dyah Puji Astuti; Siti Mutoharoh; Fatiya Husna Arkani; Nur Inayatul Afiqoh (JOMIS (Journal of Midwifery Science), 2026)
Introduction: The prevalence of lower back pain among third-trimester pregnant women in Indonesia is reported to range from 60% to 80%. If not managed with appropriate interventions, this condition can reduce the quality of life of pregnant women and interfere with their daily activities. Furthermore, untreated lower back pain may develop into prolonged chronic pain. In cases of chronic pain, management requires a multidisciplinary approach involving collaboration between physiotherapists and obstetricians-gynecologists. Methods: This study employed a quasi-experimental design with a two-group pretest-posttest design. Samples were selected using a purposive sampling technique. A total of 30 respondents were recruited for each group. The inclusion criteria were third-trimester pregnant women with a gestational age of 28–34 weeks who experienced lower back pain, did not take pain-relief medication, and were willing to participate as respondents. The exclusion criterion was pregnant women with pregnancy complications during the third trimester. Results: The mean difference test within each treatment group showed significant results (p = 0.0001). The mean reduction in lower back pain intensity was 2.2 in the Pelvic Tilt Exercise group and 1.2 in the Slow Deep Breathing group. Conclusion:Pelvic Tilt Exercise and Slow Deep Breathing were found to have a significant effect on reducing lower back pain among third-trimester pregnant women. Recommendation:Pelvic Tilt Exercise and Slow Deep Breathing can be recommended as non-pharmacological interventions to reduce lower back pain in third-trimester pregnant women